Real Picture Analysis Modules: Empowering Critical Thinking in Science Education - Amirah Nuraini Lianti Putri; Sutarto; Dwi Wahyuni; Indrawati; Iwan Wicaksono (Advances and Challenges in Science and Technology Vol. 5, 2023)
Media in learning functions to make the communication process between educators and students more effective and efficient. The use of learning media will determine the success of the learning process. Science learning requires students to have critical and analytical thinking skills. Science learning is currently geared towards fulfilling 21st century skills and is designed to be learner-centered. Modules can be a solution to realizing student-centered learning. One of the 21st century skills is critical thinking skills. This study aims to describe the process of compiling the RPA (Real Picture Analysis) module to improve students’ critical thinking skills. The RPA module is structured by integrating real images related to the science concepts being studied to develop students’ critical thinking skills. The modules are structured by referring to the stages of module preparation according to several experts and paying attention to the attainment of indicators of critical thinking. The preparation of the module goes through the stages of curriculum analysis, determining the title of the module, coding the module, and writing the module. Modules are written based on the components that must be present in a module. RPA is integrated into the core part of the module, specifically the description of the material as training material to improve students’ critical thinking skills.